Penentuan Sifat Termofisik Temu Lawak dan Temu Putih - Lamhot P Manalu; Amos Amos; Wahyu Wahyu; Purwanto Purwanto (Jurnal Litbang Industri, 2012)
The most important limitation in process design for agricultural products is the lack of information on their thermal properties. Although a lot of experimental data can be found, the variety of products and the differences in measurement method make limitation on the value of the available data, especially for Indonesia's products. These data are required to get information about temperature change when product is processed like heating or cooling. It is worth due to optimizing the efficiency of energy. The objective of this study was to determine thermal diffusivity and conductivity of java turmeric and zedoary herbs. The values were determined numerically with indirect methods. The result showed that specific heat of java turmeric and zedoary were 2.835 kJ/ kgoC and 2.863 kJ/ kgoC, thermal conductivity were 0.2797 W/moC and 0.1359 W/moC, respectively, while thermal diffusivity were 9.34x10-8 m2/s and 1.00x10-7 m2/s, respectively.ABSTRAKDalam merancang suatu sistem proses dan peralatan pengolahan hasil pertanian diperlukan pengetahuan tentang sifat-sifat panas suatu bahan diantaranya panas jenis, konduktivitas, dan difusivitas panas. Nilai-nilai tersebut untuk produk pertanian lokal sangat jarang ditemukan, sehingga dalam aplikasinya sering digunakan data sifat panas dari literatur luar yang belum tentu sesuai dan tepat dengan produk dalam negeri. Hal ini dapat menyebabkan terjadinya bias dalam perhitungan dan perancangan. Studi ini bertujuan untuk menentukan sifat-sifat/properti panas dari tanaman obat temu lawak dan temu putih. Hasil studi mendapatkan bahwa panasjenis temu lawak dan temu putih adalah masing-masing 2.835 kJ/ kgoC dan 2.863 kJ/ kgoC, konduktivitas panas masing-masing adalah 0.2797 W/moC dan 0.1359 W/moC, sedangkan nilai difusivitas panasnya masing-masing adalah 9.34x10-8 m2/detik dan 1.00x10-7 m2/detik.